4D label-free proteomics reveals that lignin and gossypol biosynthesis are enhanced in the roots of cotton (Gossypium hirsutum L. cv. TM-1) seedlings after a fifteen-days exposure to silver nanoparticles - Yuanhao Ding; Ping Li; Wenjie Lai; Yalan Li; Sihui Huang; Qiuping Zhong; Long Lu; Liyan Yin; Wei Gao; Haiyan Hu (Plant Stress)
Silver nanoparticles (AgNPs), the most extensively used nanomaterials, are inevitably released into the environment, yet their toxicological effects on plants remain not fully elucidated. To address a gap in the literature regarding the effects of AgNPs on cotton (Gossypium hirsutum L. cv. TM-1), a 15-days exposure experiment was conducted using AgNPs (10 mg/L), along with Ag+ (0.4 mg/L AgNO3) serving as a mock control and water as the control (CK). Compared to the Ag+and CK groups, the roots of cotton seedlings exposed to AgNPs showed noticeable browning with significant reductions in biomass and root length. To explore the protein-level changes in cotton root response to AgNPs, a 4D label-free proteomics analysis was performed on the AgNPs, Ag+, and CK groups. Finally, 1588 differentially expressed proteins (DEPs) unique expressed in the AgNPs-treated group, which were primarily enriched in lignin and gossypol biosynthesis pathways, as revealed by GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses. Subsequent phloroglucinol staining and quantification confirmed an increased lignin biosynthesis, while LC-MS examination demonstrated elevated gossypol production in cotton roots following AgNPs exposure. Furthermore, roots from a glandless cotton mutant (CCRI12gl, lacking gossypol) were significant shorter than those of its wide-type counterpart (CCRI12, glandular, containing gossypol) after AgNPs treatment, suggesting that gossypol enhances cotton tolerance to AgNPs. Additionally, parallel reaction monitoring (PRM) technology validated that the expression levels of proteins involved in lignin and gossypol biosynthesis were consistent with the findings of the 4D label-free proteomics analysis. This study provides new insights into the mechanisms of plant responses to AgNPs exposure and offers a fundamental reference for investigating the toxicity of nanometal in crops.